COMPUTER MODEL FOR CORRECTNESS ASSESSMENT OF ARTIFICIAL LONG LINE SYNTHESIS PROCEDURE - Pliushch, Olexander; Savchenko, Alina (Science-based technologies, 2021)
The paper considers processes that take place in pulse modulators of power amplifiers and generators. It is demonstrated that the waveform of output modulator pulse is practically completely determined by the parameters of artificial long line that is a constituent part of the modulator. It is shown that to satisfy the requirements for the pulse waveform, one needs to use heterogeneous long lines. The known procedure of such heterogeneous artificial long line synthesis is considered, which allows one to obtain a required pulse form at the modulator output. It is stressed that during this synthesis, an assumption is usually made that the line, which creates required pulse form of the current for short-circuited load, will create the required pulse form and for the discharge process through the matched impedance. An inference is made about the problem existence that lies in the fact that the mentioned assumption requires verification. The signal waveform at the output of the line requires the assessment of the waveform in the time domain as well. With account of the fact that analytical methods are hard to apply to heterogeneous long lines, the paper proposes as a solution to this problem to use a computer model. Designed computer model was applied to the known from the literature artificial long line, which is composed from five elements and aims to form trapezoidal output signal. During the trial of the artificial long line with the help of simulation computer model, it was established that artificial long line synthesis procedure allows creating the line that, while being discharged over the shot-circuited load, creates the required pulse form. At the same time, while using the model for discharge process simulation over the matched load, the waveform distorts, what points at not totally correct assumption made during the line synthesis. Designed model permits assessing the signal waveform deviation from the required one and gives a possibility to work out a decision as to this waveform improvement. Thus, developed simulation computer model allows one to assess the signal waveform in the time domain at the output of the long line for its different operation modes and check the correctness of the assumption made during the synthesis process. With account of the flexibility and the precision of the designed model, it is possible to use it for long lines parameters verification in pulse modulators, as well as for search of ways of their improvement.